Experimental study on the magnetic coherent mode in the H-mode pedestal of EAST. (27th September 2018) - Chen, Ran; Zhang, Heng; Xu, Guosheng; Zhou, Chu; Li, Yongliang; Ye, Yang; Shi, Tonghui; Liu, Haiqing; Zhang, Tao; Gao, Wei; Liu, Yong; Lyu, Bo; et al.
Abstract: Here we report the experimental analysis on the low- n (mostly n = 1, sometimes n = 2) magnetic coherent mode (MCM) at a characteristic frequency 20–, which has been frequently observed in various H-mode discharges on EAST. This mode can be easily identified in the magnetic fluctuations measured by the fast Mirnov coils mounted on the vacuum vessel wall, but is detected by the local measurements of edge electrostatic fluctuations only when the mode is sufficiently strong. The apperance of the MCM is summarized covering broad ranges of discharge parameters, in particular, the different heating schemes including pure neutral beams injected in either co- or counter-current direction as well as pure ratio-frequency waves. This may rule out the possibility of fast particle driven modes. Radial distribution and poloidal propagation of the MCM are investigated using the Doppler backscattering system and Langmuir probes inserted at the outer midplane, respectively. Temporal evolution of MCM amplitude during large ELM crashes is evaluated in detail, may suggesting the mode is closely correlated with pedestal buildup. Dedicated experiments reveal the possible correlations of MCM's frequencies with edge line-averaged density and edge safety factor q 95 . We also present the observation of multi MCMs at relatively high q 95, which are speculated locating at different rational surfaces in the pedestal via analyzing their mode structures and nonlinear interactions. Finally, effect of the MCM on edge particle transport is explored via surveying the correlation between the intermittent events of the mode and the particle fluxes deposited on the divertor target plates, utilizing the conditional analysis method. Corresponding results suggest that the MCM seems to primarily result in a notable poloidal redistribution of the divertor particle flux, rather than a considerable net increase of the total flux.